2021
DOI: 10.3390/jpm11030219
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of miR-29a in Hepatocellular Carcinoma: Implications in Mechanisms and Theragnostics

Abstract: Hepatocellular carcinoma (HCC) remains one of the most lethal human cancer globally. For advanced HCC, curable plan for advanced HCC is yet to be established, and the prognosis remains poor. The detail mechanisms underlying the progression of HCC tumorigenicity and the corruption of tumor microenvironment (TME) is complex and inconclusive. A growing body of studies demonstrate microRNAs (miRs) are important regulators in the tumorigenicity and TME development. Notably, mounting evidences indicate miR-29a play … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 92 publications
(151 reference statements)
1
15
0
Order By: Relevance
“…Our previous study confirmed that miR-29a targets multiple biological function impacts, including attenuated shoulder stiffness fibrosis [34], liver fibrosis [8,12,35], and mitigated NAFLD [14,36], as well as influenced progression of HCC formation [26]. Similar findings have been confirmed by Song et al, who showed miR-29a downregulated Bcl-2 expression to ameliorate liver tumorigenesis [35].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our previous study confirmed that miR-29a targets multiple biological function impacts, including attenuated shoulder stiffness fibrosis [34], liver fibrosis [8,12,35], and mitigated NAFLD [14,36], as well as influenced progression of HCC formation [26]. Similar findings have been confirmed by Song et al, who showed miR-29a downregulated Bcl-2 expression to ameliorate liver tumorigenesis [35].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, miR-29a decreased expression in high-risk HCC using WD/CCl4-treated mice (Figure 4A). Expanding evidence has revealed that miR-29a is indispensable in chronic liver disease [26]. We uncovered that liver tissue of mice treated with WD/CCl4 upregulated the expression of HIF-1α and Angpt2 (Figure 4B,C).…”
Section: Wd/ccl4 Treated Intervention Mir-29a Expression and Promoted...mentioning
confidence: 81%
“…Although MIR29A -activated metastasis-suppression signaling pathways involving carcinogenesis, epigenetics, metabolic adaptation, and immunomodulation in HCC have been noted [ 39 ], its role in regulating factors modeling the structure of TME was yet to be clarified. In this regard, our study identified MIR29A as a common suppressor for LOX , LOXL2 , and VEGFA , which notably present a panel of diagnostic and prognostic factors along with MIR29A.…”
Section: Discussionmentioning
confidence: 99%
“…The MIR29A expression features clinical significance in a variety of disease scenarios, including Alzheimer’s disease [ 15 ], Parkinson’s disease [ 16 ], ankylosing spondylitis [ 17 ], atherosclerosis [ 18 ], atrial fibrillation [ 19 ], active pulmonary tuberculosis [ 20 ], thoracic aneurysms [ 21 ], tendon disease [ 22 ], diabetes [ 23 ], scleroderma [ 24 ], cholestatic pediatric liver disease [ 25 ], and non-alcoholic fatty liver disease (NAFLD) [ 26 ]. Importantly, our previous studies have reported the hepatoprotective role of MIR29A in the scenario of cholestasis- or diet-induced steatohepatitis and liver fibrosis [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and growing evidence has revealed its regulatory role on HCC metastasis [ 13 , 39 ]. In terms of biological activity, MIR29A was reported to directly target VEGFA to perturb the wound healing process [ 40 ], and to directly target LOXL2 to impede tumor progression [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, migratory capacity of tumours is under modulation by miRNAs (Refs 105, 106). The miRNAs can dually suppress/induce migration of cancers.…”
Section: Micrornas and Sox2mentioning
confidence: 99%